The Role of Intellectual Capital on Financial Performance with Competitive Advantage as a Mediator - Firmansah, Rendy; Hana, Kharis Fadlullah (Jeksyah: Islamic Economics Journal, 2025)
This study aims to analyze the effect of intellectual capital on the return on assets (ROA) of Islamic Commercial Banks (BUS) in Indonesia, with competitive advantage as a mediating variable. The research is motivated by the growing importance of managing intellectual resources to enhance competitiveness and performance in an increasingly dynamic economic environment. A quantitative approach was employed using secondary data from the annual reports of 10 BUSs selected through purposive sampling for the 2016–2023 period. Data were analyzed using SmartPLS 3 software. The results show that intellectual capital does not have a significant effect on ROA and does not significantly influence competitive advantage. Furthermore, competitive advantage does not mediate the relationship between intellectual capital and ROA. However, competitive advantage has a significant positive impact on ROA. These findings indicate that while intellectual capital practices in BUSs do not directly or indirectly enhance profitability, strengthening competitive advantage remains a key driver of financial performance. The contribution of this study lies in providing empirical evidence on the mediating role of competitive advantage in the Islamic banking context in Indonesia over an extended period, offering insights for managers to strategically integrate intellectual capital development with competitiveness enhancement.